INNOVATIVE EDUCATIONAL DEVELOPMENT IN PERIOD OF THE DIGITALIZATION OF THE EDUCATIONAL PROCESS (International journal of artificial intelligence, 2026)
This article describes the current structure of the education system in the Republic of Uzbekistan, which has been reformed over the past decade in accordance with the National Program for Personnel Training adopted in the country, the educational programs at various levels implemented in Uzbekistan, the qualifications awarded upon completion, and the educational documents confirming these qualifications.